2017
DOI: 10.1590/0103-6440201701094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alox-15 Polymorphism on GCF Levels of Lipoxin-A4 in Chronic Periodontitis: A Preliminary Study

Abstract: Lipoxins play an important role in periodontal resolution, hence, investigation of genetic polymorphism of lipoxin gene may provide important information on the role of lipoxins in periodontal disease pathogenesis. The aim of this study was to investigate a polymorphism of C-to-T substitution at position c.-292 in ALOX15 (reticulocyte-type 15 lipoxygenase 1) gene in patients with chronic periodontitis and to associate the polymorphism with gingival crevicular fluid (GCF) lipoxin A4 (LXA4) levels. Forty-five ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In previous studies using GCF samples LXA4 level was reported to be lower in periodontitis, con rming that the ndings of decrease in salivary LXA4 might be an indicator of susceptibility to periodontitis [45][46][47]. Therefore, saliva level of LXA4 may be more reliable than serum in evaluating the its role in periodontitis.…”
Section: Discussionmentioning
confidence: 71%
“…In previous studies using GCF samples LXA4 level was reported to be lower in periodontitis, con rming that the ndings of decrease in salivary LXA4 might be an indicator of susceptibility to periodontitis [45][46][47]. Therefore, saliva level of LXA4 may be more reliable than serum in evaluating the its role in periodontitis.…”
Section: Discussionmentioning
confidence: 71%
“…Macrophages and neutrophils also displayed slower kinetics and decreased maximal phagocytosis of P. gingivalis and Aggregatibacter actinomycetemcomitans in patients with LgAP compared with periodontally healthy controls 59 . While some studies have reported significant decreases in lipoxin A4 levels in the GCF of patients with periodontitis, 60,61 one study has reported higher serum lipoxin A4 levels in the periodontitis group compared with healthy controls ( p < .05) 42 . The demographic properties of the study population (ie, the severity of periodontitis; lifestyle habits), differences in samples (saliva, serum, and/or GCF), and methods of analysis (ie, ELISA, high‐performance liquid chromatography) could also explain the differences in study results.…”
Section: Discussionmentioning
confidence: 99%
“…No significant association was detected between ALOX-15,c.-292 C > T polymorphism variants, and occurrence of NCFB which might pose questions about the genetic determinant’s role in disease pathogenesis. Few studies evaluated the effect of ALOX-15 gene polymorphism on LXA4 levels [ 35 ]. Also, its anti-inflammatory role was studied in animals [ 36 ].…”
Section: Discussionmentioning
confidence: 99%